Novel View Synthesis Under Large-Deviation Viewpoint for Autonomous Driving - Ma, Xin; Zhang, Jiguang; Lu, Peng; Xu, Shibiao; Pan, Chengwei (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Novel view synthesis is a critical task in autonomous driving. Although 3D Gaussian Splatting (3D-GS) has shown success in generating novel views, it faces challenges in maintaining high-quality rendering when viewpoints deviate significantly from the training set. This difficulty primarily stems from complex lighting conditions and geometric inconsistencies in texture-less regions. To address these issues, we propose an attention-based illumination model that leverages light fields from neighboring views, enhancing the realism of synthesized images. Additionally, we propose a geometry optimization method using planar homography to improve geometric consistency in texture-less regions. Our experiments demonstrate substantial improvements in synthesis quality for large-deviation viewpoints, validating the effectiveness of our approach.